The Ashford affair [compact disc, unabridged] - Willig, Lauren (Macmillan Audio, 2013)
Clementine Evans has finally achieved almost everything she's been working towards, but now she's not sure it's enough. Her long hours have led to a broken engagement and, suddenly single at thirty-four, she feels her messy life crumbling around her. But when the family gathers for her grandmother's birthday, a relative lets slip hints about a long-buried family secret.